Incorporation of teleworking during covid-19 in the most important subsectors of Ecuador - Domínguez Arias, Francis; Darquea Moreno, Bernardo (mktDESCUBRE; Vol 1 No 16 (2020): Sixteenth Edition (July - December)DO - 10.36779/mktdescubre.v1i16.526, 2020)
This study systematically analyzes the difficulties experienced in the migration from conventional work to telework. The research focused on the most important sub-sectors in the Ecuadorian economy, contextually examining the background of technological investment, the level of accessibility of the population, and the incorporation of ICTs into Ecuadorian organizational models. The data was linked to information generated by Ecuador's Ministry of Labor on the amount of telework currently operating in the country. Through a systematic review of the available literature, based on a mixed approach and with a level of descriptive study, it was possible to conclude that there are shortcomings in the incorporation of a telework model in Ecuador. With only 3.74% of the work force performing under the telework modality by July 2020 in the most important sub-sectors of the country, it is evident that these are not prepared to remain productive under the regulations of the new post-quarantine normality.